Chiral Cu(II)-catalyzed enantioselective β-borylation of α,β-unsaturated nitriles in water - Zhu, Lei; Kitanosono, Taku; Xu, Pengyu; Kobayashi, Shū (Beilstein Journal of Organic Chemistry, 2015)
The promising performance of copper(II) complexes was demonstrated for asymmetric boron conjugate addition to α,β-unsaturated nitriles in water. The catalyst system, which consisted of Cu(OAc)2 and a chiral 2,2′-bipyridine ligand, enabled β-borylation and chiral induction in water. Subsequent protonation, which was accelerated in aqueous medium, led to high activity of this asymmetric catalysis. Both solid and liquid substrates were suitable despite being insoluble in water.
Keywords: carbon–boron bond formation; catalytic asymmetric synthesis; chiral copper(II) catalysis; β-hydroxy nitriles